2022
DOI: 10.1002/acn3.51576
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological correlates of pyramidal signs in multiple system atrophy

Abstract: Objective Pyramidal signs are common but often under‐recognized in multiple system atrophy (MSA). The clinicopathological correlates of pyramidal signs in MSA are not well characterized. The present study aims to understand the role of pyramidal signs in MSA. Methods We examined 40 autopsy‐confirmed MSA cases in New York Brain Bank. The pyramidal signs were quantified by an established rating scale, summarized as the pyramidal score. We assessed whether pyramidal scores are associated with autonomic, parkinson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Unfortunately, he refused to undergo EMG studies. Recently, a study about MSA found that patients with low pyramidal scores are more likely to have erectile dysfunction ( 21 ). The association between ataxia symptoms and autonomic dysfunction in SCA3 requires future exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, he refused to undergo EMG studies. Recently, a study about MSA found that patients with low pyramidal scores are more likely to have erectile dysfunction ( 21 ). The association between ataxia symptoms and autonomic dysfunction in SCA3 requires future exploration.…”
Section: Discussionmentioning
confidence: 99%
“…123 Last but not least, an unexplained Babinski sign is listed as a supportive motor feature based on the involvement of the pyramidal system. 116…”
Section: Degenerative Causes Of Ataxiamentioning
confidence: 99%
“…123 Last but not least, an unexplained Babinski sign is listed as a supportive motor feature based on the involvement of the pyramidal system. 116 Challenges remain in differentiating MSA versus PD in the context of parkinsonism with neurogenic orthostatic hypotension. Laboratory tests such as scintigraphy with 123Imetaiodobenzylguanidine enable the quantification of postganglionic sympathetic cardiac innervation to differentiate MSA versus PD, 124 but clinical application has so far been limited because it is not widely performed in clinical settings.…”
Section: Degenerative Causes Of Ataxia Multiple System Atrophymentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple system atrophy (MSA) is a sporadic adultonset neurodegenerative disease characterized by parkinsonism, cerebellar ataxia, pyramidal signs and dysautonomia in any combination [1,2]. At disease onset, the predominant motor phenotype is either parkinsonian (MSA-P) or cerebellar (MSA-C).…”
Section: Introductionmentioning
confidence: 99%